2019
DOI: 10.1111/ejh.13215
|View full text |Cite
|
Sign up to set email alerts
|

Risks and challenges of CML management during pregnancy: Looking for a balanced decision

Abstract: On the other hand, in many situations, pregnant patients with CML may be observed without any therapy for the whole pregnancy period. New data about the kinetics of the leukemic clone during pregnancy indicate the possibility of slowly increasing BCR-ABL levels after TKI cessation. 12 Moreover, patients with non-sustained DMR and even with a major molecular response (MMR or BCR-ABL ≤0.1% IS) who lose their response when TKI is interrupted during pregnancy, restore their initial response after re-initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…Acetyl salicylic acid and/or low molecular weight heparin are indicated for thrombocytosis. Leucapheresis and/or IFNα are safe throughout gestation [122,130]. Close collaboration with obstetricians and regular fetal ultrasound examinations are recommended.…”
Section: Pregnancy and Parentingmentioning
confidence: 99%
“…Acetyl salicylic acid and/or low molecular weight heparin are indicated for thrombocytosis. Leucapheresis and/or IFNα are safe throughout gestation [122,130]. Close collaboration with obstetricians and regular fetal ultrasound examinations are recommended.…”
Section: Pregnancy and Parentingmentioning
confidence: 99%
“…Reports have recommended a collaborative approach between the patient and the hematology and obstetric teams regarding the management of pregnancy during TKI treatment for CML. Ideally, female patients with CML who wish to become pregnant should do so when in sustained molecular response and should stop therapy upon conception [ 7 , 9 , 10 , 18 , 19 ]. The effects of bosutinib on pregnancy experienced in the current study were largely similar to those reported for other TKIs, and female patients with CML should not be exposed to TKIs during pregnancy [ 5–11 , 20–23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noha az imatinibet biztonságosan alkalmazták a második és a harmadik trimeszterben, a rendelkezésre álló, igen kevés tapasztalat alapján nem javasolt a rutinalkalmazás. A TKI az anyatejbe kis koncentrációban kiválasztódik, a szoptatás ideje alatt nem javasolt a használatuk [41].…”
Section: Saját Tapasztalatokunclassified